2020
DOI: 10.1039/d0ee02020f
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous interfacial chemistry and inner Helmholtz plane regulation for superior alkaline hydrogen evolution

Abstract: Developing highly efficient and durable alkaline hydrogen evolution reaction (HER) electrocatalysts composed of earth-abundant materials is crucial for large-scale electrochemical hydrogen production. Herein, interfacial chemistry engineering is employed to decoupling...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 45 publications
4
68
0
Order By: Relevance
“…38 and 39 ). Thus, the electron mobility of the 1T phase -MoS 2 @NiS 2 catalysts was more favorable for the efficient charge transfer, which agrees consistent with the EIS test results 58 . Moreover, the PDOS results imply that the NiS 2 interface hybrid generates some new interface electronic states in 1T phase -MoS 2 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…38 and 39 ). Thus, the electron mobility of the 1T phase -MoS 2 @NiS 2 catalysts was more favorable for the efficient charge transfer, which agrees consistent with the EIS test results 58 . Moreover, the PDOS results imply that the NiS 2 interface hybrid generates some new interface electronic states in 1T phase -MoS 2 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…For Ni3N, it requires a high energy barrier of 0.33 eV for water dissociation, leading to a sluggish kinetics for the Volmer step which provides H* intermediate. It has been reported that metallic Ni possesses active sites for hydroxyl adsorption and serves as the promoter for water dissociation[64]. Our calculations have confirmed the enhanced water adsorption on Ni3N/Ni.…”
supporting
confidence: 82%
“…As a result, the V-Ni3N/Ni shows an appropriated energy of 0.14 eV for water dissociation. The adsorption energy of hydrogen (GH*) has been widely employed as a descriptor for predicting the activity of HER electrocatalysts[14,28,43,64]. Upon comparison, Ni3N and V-Ni3N exhibit a negative GH* of −0.33 and −0.24 eV, indicating the strong adsorption for H* that hinders the desorption of H2 product.…”
mentioning
confidence: 99%
“…Thus, the electron mobility of the 1T phase -MoS 2 @NiS 2 catalysts was more favorable for the e cient charge transfer, which agrees consistent with the EIS test results. 45 Moreover, the PDOS results imply that the NiS 2 interface hybrid generates some new interface electronic states in 1T phase -MoS 2 (Supplementary Fig. 15c However, H* can be absorbed not only by the 1T phase -MoS 2 @NiS 2 surface.…”
Section: Introductionmentioning
confidence: 95%